Spatiotemporal Dynamics of Covert vs. Overt Emotional Face Processing in Dysphoria - Jaspers-Fayer, Fern; Maffei, Antonio; Goertzen, Jennifer; Kleffner, Killian; Coccaro, Ambra; Sessa, Paola; Liotti, Mario (Frontiers in Behavioral Neuroscience, 2022)
Behavioral and electrophysiological correlates of the covert and overt processing of emotional expressions were investigated in healthy participants with highly dysphoria and low dysphoria. A state-of-the-art non-parametric permutation-based statistical approach was then used to explore these effects. Behaviorally, participants responded faster and more accurately when overtly categorizing happy faces and they were slower and less accurate when categorizing sad and fearful faces, independent of dysphoria group status. In an early time-window (temporo-occipital N170, 140–180 ms), there were main effects of Emotion (greater voltage amplitude for sad, fearful and happy faces relative to neutral faces), and Task (greater voltage amplitude for covert relative to overt faces). These effects did not differentiate between dysphoria groups. Instead, dysphoria status was related to greater N170 voltage amplitude over left-sided temporo-occipital scalp, independent of attentional demands. In an intermediate time-window (temporo-occipital EPN, 200–400 ms), there were main effects of Emotion, with greater voltage amplitude for happy relative to neutral and sad expressions, and Task, with greater amplitude for overt versus covert processing. Notably, there were no main effects nor interaction effects involving dysphoria group status. In a late time-window (posterior LPP, 500–750 ms), there were main effects of Emotion and Task and a significant interaction of Emotion and Task, explained by greater LPP voltage amplitudes in response to overtly attended fearful and sad expressions relative to happy expressions. Again, there were no main effects nor interaction effects involving dysphoria group status. Conclusion: This study provides novel evidence that high dysphoria differentially affects an early, automatic stage of processing of emotional faces. This modulation is independent of the top-down allocation of attention, supporting the idea that dysphoria influences a stage of automatic emotional appraisal postulated by cognitive models of depression vulnerability. This dysphoria-dependent N170 modulation appears to be an independent mechanism from the N170 emotion modulation, being present for all emotional expressions, and being left-sided. It is proposed that this effect may be a consequence of a shift from holistic to feature-based processing of facial expressions, or due to the influence of negative schemas acting as a negative context for emotional facial processing